2006
DOI: 10.3354/meps328205
|View full text |Cite
|
Sign up to set email alerts
|

Diel and tidal rhythms in diving behaviour of pelagic sharks identified by signal processing of archival tagging data

Abstract: Patterns of vertical movement in pelagic predators can be highly complex, reflecting behaviours such as foraging, thermoregulatory excursions and spawning. Here we used fast Fourier analysis to identify periodicity in the vertical movements of 6 basking sharks Cetorhinus maximus from archival tagging data that totalled 595 d. We analysed quantitatively fine-scale vertical movements of basking sharks over seasonal scales (May to February) and detected predominant periodicities related to the vertical movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 30 publications
2
83
1
1
Order By: Relevance
“…This coincides figure S2). While this distribution includes areas with colonies of endangered monk seals (Baker et al 2007), detailed dive records from four recovered satellite tags (three females and one unsexed; three separate years) indicated that the dominant behaviour, when not transiting (Weng et al 2007), was a precise diel vertical migration, between the surface and 600 m, consistent with foraging within the deep scattering layer community (Shepard et al 2006) (electronic supplementary material, figure S3). …”
Section: Resultsmentioning
confidence: 99%
“…This coincides figure S2). While this distribution includes areas with colonies of endangered monk seals (Baker et al 2007), detailed dive records from four recovered satellite tags (three females and one unsexed; three separate years) indicated that the dominant behaviour, when not transiting (Weng et al 2007), was a precise diel vertical migration, between the surface and 600 m, consistent with foraging within the deep scattering layer community (Shepard et al 2006) (electronic supplementary material, figure S3). …”
Section: Resultsmentioning
confidence: 99%
“…Intra-individual differences have been less well documented, although it is unclear whether this is because such patterns rarely occur or whether it is only recently that animals have been tracked with sufficient spatial and temporal resolution to identify such transitions (Shepard et al 2006). Recent examples indicate significant shifts in movement patterns, diving behaviour and thermal biology in Atlantic bluefin tuna at different stages of the breeding cycle ), whilst abrupt changes were observed in the swimming behaviour of individual white sharks Carcharodon carcharias (Bruce et al 2006) and in the depth use of basking sharks Cetorhinus maximus (Shepard et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples indicate significant shifts in movement patterns, diving behaviour and thermal biology in Atlantic bluefin tuna at different stages of the breeding cycle ), whilst abrupt changes were observed in the swimming behaviour of individual white sharks Carcharodon carcharias (Bruce et al 2006) and in the depth use of basking sharks Cetorhinus maximus (Shepard et al 2006). Knowing how individual behaviour varies across a range of spatio-temporal scales is an essential step towards understanding habitat selection processes in large marine animals (Sims et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Bost et al 2002, Hays 2003, Shepard et al 2006, Baumgartner & Fratantoni 2008. For large-bodied predators like baleen whales that need to feed on tremendous quantities of zooplankton each day (Kenney et al 1986), DVM can have a profound effect on a predator's ability to find sufficient food resources and to exploit those resources efficiently.…”
Section: Introductionmentioning
confidence: 99%